Professional standards for educational leaders : the empirical, moral, and experiential foundations - Murphy, Joseph, 1949- (Corwin, a SAGE publication company, 2017)
Evidence increasingly points to a direct link between the curriculum leadership provided by educational leaders and the overall effectiveness of schools. Professional Standards for Educational Leaders introduces the foundations of the recently revised professional educational leadership standards and provides an in-depth explanation and application of each one. Written by the primary architect of PSEL, educational leadership expert Joseph F. Murphy, this authoritative guide to understanding and applying the standards explores the new emphasis on: Leadership of learning, school culture, and diversity ; Values, ethics, and professional norms of educational leadership ; Teacher quality, instruction, and caring support. - Resumé vydavatel
Keywords: ředitelé škol -- Spojené státy americké; management školy -- Spojené státy americké; normy a standardy; school principals -- United States; school management -- United States; standards; elektronické knihy; příručky; electronic books; handbooks and manuals